Operating room black box: GIMMICK or a patient safety tool? - Safna Naozer Virji; Muhammad Rizwan Khan; Saleema Begum (Journal of the Pakistan Medical Association, 2024)
The Operating Room Black Box (ORBB) is a relatively recent technology that provides a comprehensive solution for assessing technical and non-technical skills of the operating team. Originating from aviation, the ORBB enables real-time observation and continuous recording of intraoperative events allowing for an in-depth analysis of efficiency, safety, and adverse events. Its dual role as a teaching tool enhances transparency and patient safety in surgical training. In comparison to traditional methods, like checklists that have limitations, the ORBB offers a holistic understanding of clinical and non-clinical performances that are responsible for intraoperative patient outcomes. It facilitates systematic observation without additional personnel, allowing for review of numerous surgical cases. This review highlights the potential benefits of the ORBB in enhancing patient safety, its role as a surgical training tool, and addresses barriers especially in resource-constrained settings. Continues...